Biosurfactant Production and Surface Translocation Are Regulated by PlcR in Bacillus cereus ATCC 14579 under Low-Nutrient Conditions - Hsueh, Yi-Huang (American Society for Microbiology (ASM), 2007)
Bacillus cereus ATCC 14579 can respond to nutrient changes by adopting different forms of surface translocation. The B. cereus ATCC 14579 ΔplcR mutant, but not the wild type, formed dendritic (branched) patterns on EPS [a low-nutrient medium that contains 7.0 g K(2)HPO(4), 3.0 g KH(2)PO(4), 0.1 g MgSO(4)·7H(2)O, 0.1 g (NH(4))(2)SO(4), 0.01 g CaCl(2), 0.001 g FeSO(4), 0.1 g NaCl, 1.0 g glucose, and 125 mg yeast extract per liter] containing 0.7% agar. The dendritic patterns formed by sliding translocation of nonflagellated cells are enhanced under low-nutrient conditions and require sufficient production of a biosurfactant, which appears to be repressed by PlcR. The wild-type and complemented strains failed to slide on the surface of EPS agar because of the production of low levels of biosurfactant. Precoating EPS agar surfaces with surfactin (a biosurfactant produced by Bacillus subtilis) or biosurfactant purified from the ΔplcR mutant rescued the ability of the wild-type and complemented strains to slide. When grown on a nutrient-rich medium like Luria-Bertani agar, both the wild-type and ΔplcR mutant strains produced flagella. The wild type was hyperflagellated and elongated and exhibited swarming behavior, while the ΔplcR mutant was multiflagellated and the cells often formed long chains but did not swarm. Thin-layer chromatography and mass spectrometry analyses suggested that the biosurfactant purified from the ΔplcR mutant was a lipopeptide and had a mass of 1,278.1722 (m/z). This biosurfactant has hemolytic activity and inhibited the growth of several gram-positive bacteria.